2009
DOI: 10.1002/hep.23034
|View full text |Cite
|
Sign up to set email alerts
|

Strain-dependent viral dynamics and virus-cell interactions in a novel in vitro system supporting the life cycle of blood-borne hepatitis C virus #

Abstract: These results suggest that this in vitro infection system can reproduce strain-dependent events reflecting viral dynamics and virus-cell interactions at the early phase of blood-borne HCV infection, and that this system can allow the development of new anti-HCV strategies specific to various HCV strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…Several reports have shown that disulfide bonds in the capsid proteins of some viruses are involved in virus particle assembly and stabilization of the viral capsid structure (4,21,27,28,57); these viruses are characterized by icosahedral nucleocapsids. Because, like these viruses, the HCV virion is spherical (2,20), it has been suggested that HCV may contain a nucleocapsid with a similar structure (20). We found the dbc-complex, which is most likely to be the dbd-core in JFH1 E2FL virus-like particles ( Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Several reports have shown that disulfide bonds in the capsid proteins of some viruses are involved in virus particle assembly and stabilization of the viral capsid structure (4,21,27,28,57); these viruses are characterized by icosahedral nucleocapsids. Because, like these viruses, the HCV virion is spherical (2,20), it has been suggested that HCV may contain a nucleocapsid with a similar structure (20). We found the dbc-complex, which is most likely to be the dbd-core in JFH1 E2FL virus-like particles ( Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Immortalized human primary hepatocyte HuS-E/2 cells were as described previously (17). Other cells and plasmids used in this experiment are summarized in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Early evidence of productive HCV infection in culture came from the use of a human hepatocellular carcinoma–derived line (FLC4) cultured in 3D radial-flow bioreactors (108). More recently, Aly and coworkers demonstrated that HCV replication was increased in immortalized primary hepatocytes cultured in a 3D thermoreversible gelatin polymer (TGP) system (109) and that viral particle production was achieved upon challenge with HCV gt1b and gt2a (110) when these cells were cultured in a 3D hollow fiber system (111). Like the TGP system, the hollow fiber reactor is smaller scale than the radial-flow bioreactor, allowing easy access to both medium and cells for virological assessment.…”
Section: Hepatotropic Virus Infection In Models With Emergent Propertiesmentioning
confidence: 99%